2020
DOI: 10.1111/codi.14952
|View full text |Cite
|
Sign up to set email alerts
|

Further insights into the treatment of perineal hernia based on a the experience of a single tertiary centre

Abstract: Aim There is little evidence concerning the optimal surgical technique for the repair of perineal hernia. This study aimed to report on the evolution of a technique for repair of perineal hernia by analysing the experience in a tertiary referral centre. Method This was a retrospective review of consecutive patients who underwent perineal hernia repair after abdominoperineal excision in a tertiary referral centre. The main study end‐points were rate of recurrent perineal hernia, perineal wound complications and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…The study also builds on an earlier study published in 2016 which reported the institution’s experience with biological meshes in perineal hernias [6]. The high recurrence rates with biological meshes led to a practice change, replacing biological meshes with its synthetic counterpart [5]. With the benefit of hindsight, the high recurrence rate is probably to be expected.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…The study also builds on an earlier study published in 2016 which reported the institution’s experience with biological meshes in perineal hernias [6]. The high recurrence rates with biological meshes led to a practice change, replacing biological meshes with its synthetic counterpart [5]. With the benefit of hindsight, the high recurrence rate is probably to be expected.…”
mentioning
confidence: 82%
“…In this issue of the journal, Blok et al . [5] report a single centre experience with perineal hernia over a 10‐year period. Although the study only comprises 34 patients, it is one of the larger studies on perineal hernias.…”
mentioning
confidence: 99%
“…However, the choice of treatment depends on the symptoms and how they affect the day to day life of the patient. Patients who are fit for surgery, have no recurrency, and are bothered or have severe symptoms (perineal swelling, perineal skin necrosis, urinary problems and/or intestinal obstruction) are offered surgical treatment [4,14,17,19].…”
Section: Management Of Perhmentioning
confidence: 99%
“…The aim of surgical repair is to exclude recurrency, closure of the pelvic defect with reconstruction of a new pelvic floor and reduction of hernial sac content and/or excision of hernial sac [4,16,17,19,23]. Imaging with MRI and endoscopy may help exclude recurrency [17].…”
Section: Aim Of Perh Repairmentioning
confidence: 99%
See 1 more Smart Citation